Use of vacuum-assisted closure in treatment of intestinal fistula – case report - Spychała, Arkadiusz; Murawa, Dawid; Nowaczyk, Piotr; Połom, Karol (Contemporary Oncology/Współczesna Onkologia, 2008)
Intestinal fistulae are severe complications of gastrointestinal tract operations. Vacuum-assisted closure is one method to treat them. VAC promotes wound healing by increased blood flow through the wound, faster granulation, removal of excess wound fluid and decrease in bacterial colonization. Nowadays the method is commonly used in treatment of stomach compartment syndrome, infected wounds, leg ulceration, as supportive therapy in skin grafting and burn wounds. Another application of the device is intestinal fistula. The aim of the report is case presentation of a patient with intestinal fistula successfully treated by vacuum-assisted closure.